Pengembangan Papan Komposit dari Limbah Perkebunan Sagu (Metroxylon sago Rottb.) (Development of Composite Board made from Sago (Metroxylon sago Rottb.) Plantation Waste) - Sukma S Kusuma; Ruslan Ruslan; Muhammad Daud; Ika Wahyuni; Teguh Darmawan; Yusup Amin; Muh. Y Massijaya; Bambang Subiyanto (Jurnal Ilmu dan Teknologi Kayu Tropis, 2010)
Plantation waste has gained increasing attention as an alternative raw material for use in the manufacture of composite boards, i.e. waste of sago plantation. Medium density composite boards were made from zephyr of sago midrib to evaluate the effects of resin and adhesive content levels. The boards were fabricated using polyurethane (PU) and phenol formaldehyde (PF) resin with three levels of adhesive content i.e. 10%, 12%, and 14%. Physical (moisture content, density, water absorption, and thickness swelling) and mechanical (Modulus of Rupture, Modulus of Elastisity, Screw Holding, and Internal Bonding) properties of composite board were evaluated according to JIS A 5908-2003 standard. Research result showed that properties of composite board made from sago frond with 14% content level of polyurethane adhesive better than other composite board. Based on composite board properties, the board was suitable as building raw material and furniture i.e. partition, cupboard, table, and roof.